2016
DOI: 10.1519/jsc.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Propulsive Force in Tethered Swimming and 200-m Front Crawl Performance

Abstract: Santos, KB, Bento, PCB, Pereira, G, and Rodacki, ALF. The relationship between propulsive force in tethered swimming and 200-m front crawl performance. J Strength Cond Res 30(9): 2500-2507, 2016-The aims of this study were to determine whether propulsive force (peak force, mean force, impulse, and rate of force development) and stroke rate change during 2 minutes of front crawl tethered swimming and to correlate them with the stroke rate and swimming velocity in 200-m front crawl swimming. Twenty-one swimmers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
3
12
0
1
Order By: Relevance
“…Our swimmers presented similar but independent contralateral symmetry during swimming and dryland testing. The very strong relationship between isokinetic and tethered forces supports the assertion that isokinetic ones are related to swimming performance and reinforced that the 30 s tethered swimming test is a good predictor of swimming performance [6,17]. Swimmers showed a similar force production between preferred and nonpreferred body sides (both in tethered front crawl and backstroke swimming) and isokinetic tests (Table 2; p = 0.18 to 0.97).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our swimmers presented similar but independent contralateral symmetry during swimming and dryland testing. The very strong relationship between isokinetic and tethered forces supports the assertion that isokinetic ones are related to swimming performance and reinforced that the 30 s tethered swimming test is a good predictor of swimming performance [6,17]. Swimmers showed a similar force production between preferred and nonpreferred body sides (both in tethered front crawl and backstroke swimming) and isokinetic tests (Table 2; p = 0.18 to 0.97).…”
Section: Discussionsupporting
confidence: 64%
“…Analyzing swimmers' force production should be a priority in their training control and research, as an effective propulsion is fundamental for competitive success [1][2][3]. For this purpose, tethered swimming has been one of the most frequently used methods, yielding substantial associations between tethered forces and swimming performance in sprint events [4][5][6]. These studies underpin the notion that movements used in training and testing should be mechanically similar to those used in competition [7].…”
Section: Introductionmentioning
confidence: 99%
“…For such purposes, researchers and coaches have been widely using tethered swimming to measure/quantify the net forces throughout the stroke cycle, due to its specificity and sensitivity on monitoring swimming training adaptations, without significant changes in stroke and physiological responses compared to free-swimming [17,41]. For instance, it has recently been shown that peak force in tethered swimming is moderately correlated (r = 0.61) with 200-m crawl swimming performance [48]. Higher correlations are expected when shorter distances are used, as neuromuscular abilities (i. e., maximum muscle strength and power) predominate over aerobic endurance.…”
Section: Introduction ▼mentioning
confidence: 99%
“…Neste tocante, foram encontrados diversos artigos tratando da força, dentre eles devese citar a contribuição relativa da força dos braços e pernas na natação amarrada (TOR; PEASE; BALL, 2015), além de estudos sobre as taxas de força de braçada do nado amarrado (SANTOS et al, 2016). Em outro trabalho, com nado amarrado, o objetivo foi identificar as relações entre desempenho competitivo e forças de amarração de acordo com a distância, nos quatro nados, e analisar se os valores relativos da produção de força são mais determinantes do desempenho da natação que os valores absolutos.…”
Section: Discussionunclassified